Perspective: Collagen induced platelet activation via the GPVI receptor as a primary target of colchicine in cardiovascular disease - Pennings, Gabrielle J.; Reddel, Caroline J.; Chen, Vivien M.; Gnanenthiran, Sonali R.; Kritharides, Leonard (Frontiers in Cardiovascular Medicine, 2023)
Colchicine has been demonstrated to reduce cardiovascular death, myocardial infarction (MI), ischemic stroke, and ischemia-driven coronary revascularization in people with coronary artery disease (CAD). These reductions were observed even in patients already taking antiplatelet therapy. As well as having anti-inflammatory effects, colchicine demonstrates antiplatelet effects. We propose that colchicine's antiplatelet effects primarily target collagen-induced platelet activation via the collagen receptor, glycoprotein (GP)VI, which is critical for arterial thrombosis formation. In settings such as stroke and MI, GPVI signaling is upregulated. We have demonstrated in vitro that therapeutic concentrations of colchicine lead to a decrease in collagen-induced platelet aggregation and alter GPVI signaling. Clinical studies of colchicine given for 6 months lead to a significant reduction in serum GPVI levels in CAD patients, which may ameliorate thrombotic risk. Future evaluation of the effects of colchicine in clinical trials should include assessment of its effects on collagen-mediated platelet activation, and consideration be given to quantifying the contribution of such antiplatelet effects additional to the known anti-inflammatory effects of colchicine.